Exploitation of geothermal energy using tunnel lining technology in a mountain environment. A feasibility study for the Brenner Base tunnel – BBT. (November 2017) - Tinti, Francesco; Boldini, Daniela; Ferrari, Marco; Lanconelli, Matteo; Kasmaee, Sara; Bruno, Roberto; Egger, Harald; Voza, Antonio; Zurlo, Raffaele
Highlights: Tunnels can be used to exploit geothermal energy. Closed loop systems are flexible to be installed in different type of tunnels. Estimation of temperature is fundamental to assess energy potential of tunnels. Energy lining is a cost-effective solution for drill-and-blast excavated tunnels. The investigation of issue of final users is fundamental in energy lining projects. Abstract: Mountain tunnels can be a direct and indirect source of geothermal energy thanks to the use of drainage water or the so-called thermal tunnel lining, respectively. The amount of available energy at the tunnel entrance depends on the hydrogeological and thermal properties of the rock-mass and the geometrical and technical characteristics of the tunnel (geometry, length, lining materials, excavation methods). Typically, the analysis of all these factors argues in favour of one solution rather than another. The paper presents an overview of the practice of energy lining, suggesting a procedure for the estimation of underground temperatures in mountain environments affected by the presence of a tunnel. The estimation procedure is applied to a preliminary design of energy lining application for the already excavated Mules Access Tunnel, part of the Brenner Base Tunnel (BBT), which will connect Fortezza (IT) to Innsbruck (AT). The study starts by collecting data on the geology, hydrogeology and temperature distribution of the investigated area as well as geometrical and mechanical details of the adopted tunnel sections. Kriging techniques are applied to obtain a three-dimensional temperature model from available information. The study defines several energy lining geometries and selects the most feasible one for practical implementation. An assessment of the energy and pressure drops to be expected at the tunnel entrance for the different circulation and operational modes is presented. The specific topic of end-user needs for the BBT situation are finally discussed.